The Effect of Mindfulness-Based Stress Reduction (MBSR) Therapy on Reducing Stress and Fatigue among Career Women - Norizan Binti Yusof; Mardiana Mansor; Haslinda Hasyim (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Working women frequently encounter high stress levels due to the combined demands of professional duties and household responsibilities. Emotional fatigue, often underestimated, plays a critical role in reducing well-being and workplace productivity. Objective: This study investigates the effectiveness of mindfulness techniques in reducing fatigue and alleviating stress among working women. Method: A qualitative case study was conducted with five professional women who also manage domestic roles. Data were collected through in-depth interviews and observations during a series of mindfulness sessions. Result: Fatigue was found to stem not only from workplace demands but also from emotional strain at home. Participants who felt unappreciated, described as experiencing a hypo emotional tank, tended to carry negative emotions into their work, increasing stress and lowering performance. After mindfulness practice, most participants reported improved emotional balance, enhanced self-worth, and noticeable reductions in fatigue and stress. Conclusion: Mindfulness practices help working women manage stress and fatigue by fostering self-awareness and emotional resilience. Contribution: This study offers insights into the emotional burdens faced by working women and supports mindfulness as an effective intervention for improving psychological well-being and job performance.